Out of the ashes [large type] - Peterson, Tracie; Woodhouse, Kimberley, 1973- (Peterson, Tracie. Heart of Alaska, 2018)
After the death of their father, Collette and Jean-Michel Langelier are no longer tied to post-war France. While his sister dreams of adventure, Jean-Michel is hoping to finally escape reminders of the horrors he faced in the war. When Jean-Michel receives an unexpected invitation for them to visit Alaska and the Curry Hotel, it seems an opportunity for a change he needs. Katherine Demarchis is a young widow who does not grieve the dangerous husband she was forced to marry. Now she just wants to retreat to a quiet life, content to be alone. First, though, she's agreed to accompany her grandmother on a final trip, but never expects to see a man from her past. Katherine and Jean-Michel once shared a deep love that was torn apart by forces beyond their control. Reunited now, have the years changed them too deeply to rediscover what they had? And when Jean-Michel's nightmares return with terrifying consequences, will faith be enough to heal what's been broken for so long?